DEVELOPING BIOLOGY LEARNING TOOL OF GUIDED DISCOVERY MODEL TO INCREASE JUNIOR HIGH SCHOOL STUDENTS’ LEARNING RESULT EXCRETORY SYSTEM MATERIAL - Wijaya, Alexander Chandra; Kardi, Soeparman; Supardi, Z A Imam (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The study aims to develop the feasibility learning material based on guided discovery models on the excretory system to improve student’s learning outcomes based on the aspect of validity, practically, and effectiveness. The development of teaching material to follow 4-D model with the trial design was one group pretest posttest design. The teaching material developed in this research were the lesson plan, student book, student worksheet, and achievement test. The teaching material were tested on 30 student of VIII grade. Data were collected using validation, observation, test, and questionnaire methods and analyzed descriptively. The results showed that: (1) the validity of the teaching material developed (lesson plans, student book, student worksheet, and achivement test) were valid category; (2) practicality in term of legability student book and students worksheet were classified good while, student activities indicated that the student learning centered, and student positively responded to the learning process; (3) the effectiveness in terms of student learning outcomes both from the aspect of cognitive, skill, and attitudes of achieve mastery. Based on the above results it could be concluded that the biology teaching material guided discovery models to improve student learning outcomes were valid, practical, and effective, so it was feasible to use in learning process.